2014
DOI: 10.4028/www.scientific.net/amr.931-932.671
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Fuel Switching to the Level of Air Toxic and its Potential Health Impact in Bangkok, Thailand

Abstract: The annual arithmetic mean concentrations of benzene and 1, 3-butadiene were gradually decreasing tendency from the year 2008 2011 at every monitoring stations in Bangkok. Dramatically decreasing of these air toxics, measured in the road curbside areas were found in the year 2012 when the Thais government implemented the improvement of fuel quality from Euro 2 to Euro 4 standards. Calculated cancer risk of benzene and 1, 3-butadiene dramatically decreased at every monitoring stations. The results indicated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The results indicated that the population was estimated to receive an excess lifetime cancer risk less than 1x10 -5 at two stations, which is proposed as the permissible maximum value by Japan Ministry of the Environment (Higashino, Mita, Yoshikado, Iwata, & Nakanishi, 2007;Thongkum & Thepanondh, 2014). However, the cancer risks in the year 2012 were found significantly decreased which indicated a success of utilization of better fuel quality to the reduction of air toxic concentration.…”
Section: Figure 3: Cancer Risk Of Benzene In Chiang Maimentioning
confidence: 78%
See 1 more Smart Citation
“…The results indicated that the population was estimated to receive an excess lifetime cancer risk less than 1x10 -5 at two stations, which is proposed as the permissible maximum value by Japan Ministry of the Environment (Higashino, Mita, Yoshikado, Iwata, & Nakanishi, 2007;Thongkum & Thepanondh, 2014). However, the cancer risks in the year 2012 were found significantly decreased which indicated a success of utilization of better fuel quality to the reduction of air toxic concentration.…”
Section: Figure 3: Cancer Risk Of Benzene In Chiang Maimentioning
confidence: 78%
“…The excess lifetime cancer risk of the population was calculated as the product of the benzene level and the unit risk for benzene. The results indicated that the population was estimated to receive an excess lifetime cancer risk greater than 1.0x10 -5 , which is proposed as the permissible maximum value for individual excess lifetime cancer risk by the Japan Environmental Agency (JEA) (Thongkum & Thepanondh, 2014).…”
Section: Resultsmentioning
confidence: 96%